2020
DOI: 10.3892/ijmm.2020.4517
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‑derived factor facilitates NLRP3 inflammasome activation through downregulating cytidine monophosphate kinase 2: A potential treatment strategy for missed abortion

Abstract: A number of conditions may underlie the occurrence of missed abortion (MA), including inflammation. Pigment epithelium-derived factor (PEDF) is a novel mediator of the inflammation-related nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome, which is associated with several human diseases. However, the association between MA and NLRP3 inflammasome, and whether PEDF is reduced in MA, remain unknown. In the present study, the decidua and chorion tissues of patients who had suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…LPS, a classic TLR4 agonist, has long been used to make preeclamptic models for years as LPS amplifies the TLR4/NF- κ B signaling to trigger trophoblastic inflammation [ 39 , 40 ]. Consistent with the latest research [ 37 , 52 ], our results showed that LPS significantly activated the TLR4/NF- κ B signaling, further contributing to the NLRP3 inflammasome-induced pyroptosis. Because of the release of the proinflammatory factors IL-1 β and IL-18, the NLRP3 inflammasome-induced pyroptosis is not only a crucial way to induce trophoblastic death in the preeclamptic placentas but also a possible amplifier of maternal systematic injury via triggering sterile inflammatory cascades.…”
Section: Discussionsupporting
confidence: 93%
“…LPS, a classic TLR4 agonist, has long been used to make preeclamptic models for years as LPS amplifies the TLR4/NF- κ B signaling to trigger trophoblastic inflammation [ 39 , 40 ]. Consistent with the latest research [ 37 , 52 ], our results showed that LPS significantly activated the TLR4/NF- κ B signaling, further contributing to the NLRP3 inflammasome-induced pyroptosis. Because of the release of the proinflammatory factors IL-1 β and IL-18, the NLRP3 inflammasome-induced pyroptosis is not only a crucial way to induce trophoblastic death in the preeclamptic placentas but also a possible amplifier of maternal systematic injury via triggering sterile inflammatory cascades.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the retention of the embryo sac in the uterus can result in the organization of soft tissues and close adhesion with the uterine wall, increasing the difficulty of detaching both, which can often cause incomplete clearance and result in continuous vaginal bleeding or infection. Some patients even require multiple clearings, which carry a higher risk of complications and even secondary infertility [ 12 , 13 ]. In this study, the combination of different drugs was used to treat MA patients, and the results showed that the time to embryo expulsion, duration of surgery, intraoperative bleeding, duration of vaginal bleeding, and bleeding volume were lower in the research group than in the control group, while the rate of complete abortion and primary curettage were significantly higher than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 inflammasome plays a central role in many acute and chronic inflammatory and degenerative diseases ( 35 38 ), but the mechanisms that control its activation are poorly understood. Recent studies have confirmed that CMPK2 plays a key role in NLRP3 activation, IL-1β production, and subsequent chronic inflammatory disease ( 26 , 27 ). We examined CMPK2 expression and NLRP3 inflammasome activation following SCI.…”
Section: Discussionmentioning
confidence: 94%